The Covid-19 Pandemic Global Risks and Uncertainties - Susam, Nazan (Istanbul University Press, 2020)
The World Health Organization's declaration of the COVID-19 disease as a pandemic as of 11 March 2020 has been considered the beginning of the fight against a new crisis for all countries. The COVID-19 pandemic is a health crisis. With the beginning of the process, protecting human health and efforts for avoiding possible excess capacity in the health system has been the priority of all countries. In this context, the first measures taken to reduce the damage caused by the virus are aimed at enhancing the health system. In order to prevent the collapse of the health system and slow down the spread of the disease, initial restrictions were put in force regarding social mobility, and in the second stage, financial measures were started to reduce the economic contraction that would create the crisis. In this process, while countries are closing borders to the world along with imposing social restrictions, these social restrictions in many countries were gradually being relaxed starting from June 2020, as financial measures have continued to be increased. At the stage we have come to, the most important word that combines the different dimensions of the COVID-19 pandemic, which has strongly affected all societies, is uncertainty, and the risks that countries are facing. Although the concept of "uncertainty" has a meaning that covers risk, "risk" is more often encountered as one of the main determinants of human activity. As long as there is uncertainty about the size of the pandemic and how long it will last, risks to activities in the economy and social life will also increase. Uncertainties remain, both in terms of health and in terms of other effects due to the pandemic. The state of uncertainty prevails, in terms of human health and other effects of the pandemic. The uncertainties related to economic variables and economic recession risks have increased especially due to the social limitations that aim to prevent the spread of the virus. This process is a long lasting one and each stage may be the subject of different studies. The continuation of the process requires short-term, periodic elaborations. This study, which mainly analyzes the first effects of the pandemic, is important in terms of being able to follow the social and economic developments in the process. A total of ten chapters in the book were prepared to draw attention to the risks and uncertainties experienced in the pandemic process from an economic, financial, social and political point of view.